Strategi Media JPNN.Com dalam Upaya Menyeimbangkan Churnalism dan Jurnalisme dalam Pemberitaan - Nadia Yuliana; Reza Safitri; Anang Sujoko (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The digital era has an impact on changing new work patterns in journalism, "Churnalism" is a new journalism that occurs as a consequence of the development of digital technology in the modern era. Churnalism is the simplicity of the way to obtain journalistic news content caused by technological advances. Churnalism threatens the quality of news in the digital era. JPNN.com is a news media that was established in 2008, experiencing a transition from the print media era to digital media. This research focuses on finding out and understanding JPNN.com media strategies in balancing Churnalism and journalism. This research is a qualitative research with a descriptive analysis approach, aiming to understand the process of Churnalism practice JPNN.com and understand their strategies in an effort to balance Churnalism and journalism. The results of this study show that JPNN.com has its own strategy in balancing Churnalism and journalism, namely a combination strategy, combining the practice of Churnalism with conventional journalism practices. The implementation of the combination strategy is carried out in six stages, including: First, journalists select potential news materials from online sources. Second, journalists research news materials to ensure the validity of the news. Third, journalists confirm with the source. Fourth, journalists combine Churnalism and conventional journalism in the reporting process. Fifth, the editor maintains the Gatekeeper function through news selection. Sixth, the editorial management conducts news every day.